Comparison of the Efficacy of Homemade and Industrially Made ANFO Explosives as an Improvised Explosive Device Charge - Lucia Figuli; Vladimir Kavicky; Stefan Jangl; Zuzana Zvakova (Communications - Scientific letters of the University of Zilina, 2018)
More than 95 % of all the terrorist attacks are carried out using the ANFO explosives. The ANFO explosives are explosives made from ammonium nitrate and fuel oil. They can be in three different variants (ammonium nitrate with oil, ammonium nitrate with oil and aluminium powder or ammonium nitrate with oil and TNT). This paper describes analysis of the field test results of ANFO explosives of different types. The efficacy of industrially made and the homemade ANFO explosives is compared and their possible usage in terrorist attacks for the treatment or the damage of critical infrastructure elements is described.